Pengaruh Seminar dan Diskusi Interaktif tentang Komitmen Organisasi terhadap Perilaku Lulusan dalam Meningkatkan Kinerja di Akademi Kesehatan John Paul II Pekanbaru - Maria, Anna (Abdimas Indonesian Journal, 2024)
The absorption and performance of graduates are part of the outcomes that must be achieved by every college, including Akademi Kesehatan John Paul II Pekanbaru (AKJP II Pekanbaru). Users of graduates hope to get workers who have insight, skills, and work behavior that can adapt to the vision, mission, and goals of the organization. Therefore, Akademi Kesehatan John Paul II Pekanbaru carries out activities to make graduates ready to work apart from trying to achieve the target of competent students in the national competency test to graduate on time. Because of that, AKJP II Pekanbaru held an interactive seminar and discussion activity "The Influence of Organizational Commitment on Organizational Behavior" for 2022/2023 graduates which was held on January 14, 2021. The activities was held at AKJP II Pekanbaru started with the opening, delivery of material, and interactive dialogue. Through this activity, participants understand the importance of an employee having an organizational commitment, which means the employee has an emotional bond with the employing organization and wants to remain part of the organization. Employees who have organizational commitment will behave in accordance with the vision, mission and goals of the organization. Organizational behavior must be realized so that an employee can gain job satisfaction for himself and have a positive impact on the organization.